2022
DOI: 10.3390/cancers14225547
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Campaign in Cancer Patients and Healthcare Workers-Results from a French Prospective Multicenter Cohort (PAPESCO-19)

Abstract: In this prospective, real-life cohort study, we followed 523 cancer patients (CP) and 579 healthcare workers (HCW) from two cancer centers to evaluate the biological and clinical results of the COVID-19 vaccination campaign. Seventy percent of the CP and 90% of the HCW received an mRNA vaccine or the AZD1222 vaccine. Seropositivity was high after the first vaccine among HCW and poor among CP. The second dose resulted in almost 100% seropositivity in both cohorts. Antibody response was higher after the second i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…We showed that both populations (CPs and HCWs) had a similar prevalence of COVID-19 infection, noted the major diagnostic importance of anosmia and the high proportion of asymptomatic cases among CPs, and demonstrated that the seropositivity, high after the first vaccine among HCWs and low among CPs, was close to 100% after the second injection in both populations. Unfortunately, we, as others, observed some infections in vaccinated populations [12][13][14]. The aim of the present article is to describe these vaccine breakthrough infections in both cohorts.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…We showed that both populations (CPs and HCWs) had a similar prevalence of COVID-19 infection, noted the major diagnostic importance of anosmia and the high proportion of asymptomatic cases among CPs, and demonstrated that the seropositivity, high after the first vaccine among HCWs and low among CPs, was close to 100% after the second injection in both populations. Unfortunately, we, as others, observed some infections in vaccinated populations [12][13][14]. The aim of the present article is to describe these vaccine breakthrough infections in both cohorts.…”
Section: Introductionmentioning
confidence: 78%
“…This section has been reported previously [12][13][14]. The PAPESCO-19 (Patients et Personnels de Santé des Centres de Lutte Contre le Cancer pendant l'épidémie de COVID- 19) prospective multicenter cohorts study took place in 4 French Comprehensive Cancer Centers, located in Angers, Clermont-Ferrand, Nancy, and Nantes.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from the PAPESCO-19 (PAtients et PErsonnels de Sante ´des Centres de Lutte Contre le Cancer pendant l'e ´pide ´mie de COVID-19), a multicenter cohort study that took place in 4 French Comprehensive Cancer Centers, located in Angers, Clermont-Ferrand, Nancy, and Nantes, as previously reported [22,23]. Participants were eligible irrespective of whether they had COVID-19 symptoms or not.…”
Section: Methodsmentioning
confidence: 99%